Enhancement of γ-aminobutyric acid, avenanthramides, and other health-promoting metabolites in germinating oats (Avena sativa L.) treated with and without power ultrasound. (15th June 2019) - Ding, Junzhou; Johnson, Jodee; Chu, Yi Fang; Feng, Hao
Highlights: Germination increased γ-aminobutyric acid, avenanthramide, and free sugar content in oats. Ultrasonication improved GABA-shunt and antioxidant ability of germinated oats. Ultrasonication enhanced avenanthramide content in germinated oats. Ultrasound treatment altered the internal and structure micro-surface of oats. Abstract: Power ultrasound as an emerging processing technology has been investigated for stimulating seeds to enhance germination and accumulation of health-promoting metabolites, such as γ-aminobutyric acid (GABA) and phenolic compounds. This work was undertaken to evaluate the effects of power ultrasound (25 kHz) on the nutritional properties of germinated oats, and the microstructure of oat groats after treatment. The changes in the external and internal microstructures of the ultrasound-treated oats kernel were investigated using Environmental Scanning Electron Microscopy (ESEM) and 3D X-ray Micro Computed Tomography (Micro-CT). Physicochemical properties of oats including GABA, free sugars, avenanthramides, total phenolic content, and antioxidant capacities were enhanced after germination. Furthermore, the power ultrasound treatment for 5 min after soaking significantly enhanced the GABA (48–96 h), alanine (24–96 h), succinic acid (48–72 h), total phenolic content (24 h), and total avenanthramides (24 h) in the germinated oats.